Toxoplasma gondii and Neospora caninum infections in goat abortions from Argentina - Unzaga, Juan Manuel (2014)
The aims of this study were to identify the occurrence of Toxoplasma gondii and Neospora caninum abortions in goats from Argentina by serological, macroscopical and microscopical examination and bioassay, and to characterize the obtained isolates by molecular techniques. For this purpose, 25 caprine fetal fluids, 18 caprine fetal brains and 10 caprine placentas from 8 dairy/meat goat farms from Argentina were analyzed. Gestational age of the aborted fetuses was determined in 18 cases. Protozoal infections were detected by at least one of the applied diagnostic techniques in 44% (11/25) of examined fetuses; specifically, 24% (6/25) were positive to T. gondii, 8% (2/25) were positive to N. caninum and 12% (3/25) were positive to both parasites. In this study IFAT titers were similarly distributed in younger and older fetuses. Macroscopical and microscopical examination of one placenta revealed chalky nodules in the fetal cotyledons and normal intercotyledonary areas, as well as necrosis and calcification of mesenchymal cells in villi. Tachyzoites were observed in peritoneal wash from 2 mice inoculated with brain and a pool of brain and placenta of two fetuses. Cell culture growth of tachyzoites was achieved from one inoculated mouse, and confirmed as T. gondii by PCR. The T. gondii isolate was identified as atypical or non-canonical by nested-PCR-RFLP. This is the first study that investigated the involvement of N. caninum and T. gondii in cases of goat abortion in Argentina.